1999
DOI: 10.3354/meps176205
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall stimulation of primary production in western Atlantic Ocean waters:roles of different nitrogen sources and co-limiting nutrients

Abstract: Using shipboard bioassays, w e examined the roles rainfall, individual and combined nutrients play in accelerating primary production in coastal, Gulf Stream and pelagic (Sargasso Sea) locations in the North Atlantic Ocean off North Caroli.na, USA, from 1993 to 1995. Photosynthetic CO, fixation and net chlorophyll a (chl a) production were measured In replicated bioassays to assess individual and combined impacts of d~fferent constituents of atmospheric deposition, including natural rainfall, a synthetic rain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 35 publications
4
46
1
1
Order By: Relevance
“…3) decreased, slowly at first, to reach their lowest level 2-3 d after the event. There is at least one documented example of rainfall stimulation of primary production at both coastal and offshore locations (Paerl et al 1999) that was attributed to the supply of inorganic N and colimiting micronutrients (e.g., Fe). In our experiment, also, the rain was likely a source of dissolved N (Table 1) and micronutrients (Tables 4-6) to the bags and fjord.…”
Section: Discussionmentioning
confidence: 99%
“…3) decreased, slowly at first, to reach their lowest level 2-3 d after the event. There is at least one documented example of rainfall stimulation of primary production at both coastal and offshore locations (Paerl et al 1999) that was attributed to the supply of inorganic N and colimiting micronutrients (e.g., Fe). In our experiment, also, the rain was likely a source of dissolved N (Table 1) and micronutrients (Tables 4-6) to the bags and fjord.…”
Section: Discussionmentioning
confidence: 99%
“…Once ignored in most nutrient budgets, studies by Paerl and colleagues clearly showed that rain could stimulate the growth of phytoplankton in marine areas where N was depleted (e.g., Paerl et al 1999). However, for inshore coastal waters and land, other inputs are often more important than atmospheric deposition.…”
Section: Increases In Human Populations and Wastewater Inflows-mentioning
confidence: 99%
“…Given the high amount of biogeochemically-relevant elements contained in the continental crust (Wedepohl, 1995), the atmosphere is vehicle of a significant (or even dominant) transport of natural and anthropogenic nutrients, and trace metals, from continents to ocean surface (Duce et al, 1991;Guerzoni et al, 1999;Paerl et al, 1999). By affecting nutrient concentration and supply in surface waters, atmospheric dust deposition can impact phytoplankton physiology (e.g., photosystem [PS] II functioning, and adjustments in PSII:PSI stoichiometry; Strzepek and Harrison, 2004;Behrenfeld et al, 2009) and ecology (e.g., cell size and community structure; Eppley and Peterson, 1979;Finkel et al, 2010), as well as ocean productivity and carbon sequestration (e.g., Jickells et al, 2005;Mahowald et al, 2005).…”
Section: Giovagnetti Et Al: Assessing the Role Of Dust Depositionmentioning
confidence: 99%